A STUDY ON INDIAN TELECOMMUNICATION INDUSTRY – AN OVERVIEW (International Journal of Food and Nutritional Sciences, 2022)
The Indian telecom industry has seen substantial transformation in the last 13 years. From being the darling of investors in 2007, it is now one of the industries with the highest levels of debt in the nation. The study generated 11 research hypotheses based on prior literature. The research is based on 11 Indian telecommunications industries that are publicly traded. The data were gathered from the financial statements of the companies. The goal of this research is to find out how financial factors affect corporate performance. In light of this, the current research examines the financial performance of eleven telecommunications businesses over the course of five years, from “2017-2021.” It depicts Economic Uncertainty Policy and Return on Asset by analyzing The connection between dependent and independent factors.Telecommunication, Industry, Return on Investment, Economic Policy Uncertainty